Severity and Outcomes of Dengue in Hospitalized Jamaican Children in 2018–2019 During an Epidemic Surge in the Americas - Lue, Aileen May; Richards-Dawson, Michelle-Ann Elizabeth Hue; Gordon-Strachan, Georgiana Marie; Kodilinye, Syed Matthew; Dunkley-Thompson, Jacqueline Anne Theresa; James-Powell, Tracia Dahlia; Pryce, Curtis Alphonso; Mears, Chadwic De'sean; Anzinger, Joshua James; Webster-Kerr, Karen; Christie, Celia Dana Claire (Frontiers in Medicine, 2022)
Objective: In 2019, dengue was among the “top-ten threats to global health”, with 3.1 million cases reported from the Americas, the highest ever. Simultaneously, Jamaica reported its largest dengue outbreak in 40 years, following Chikungunya and Zika virus epidemics, 2014 and 2016-2017, respectively. We describe dengue in children admitted to five hospitals in Jamaica during August 2018 through September 2019. Methods: Hospitalized children with dengue were managed using PAHO/WHO criteria. Data were extracted from questionnaires, entered into a dataset on Microsoft Excel version 2016, exported to SPSS version 20 and analyzed. Groups were compared using Student’s t-test for normally distributed parametric data. Chi-square analysis, or Fisher’s exact test was used for categorical variables. A p-value <0.05 was considered statistically significant. Results: There were 339 children, 245 (72.3%) aged 1-10 years, males:females 1:1. Classification was "dengue without warning signs" 53 (15.3%), "dengue with warning signs" 218 (64.3%) and "severe dengue" 68 (20%). Co-morbidities were reported in 88 (26%). Hemoglobin SC disease was associated with severe dengue with hemorrhage (p=0.005). Organ-system involvement occurred in 334 (98.5%) including gastrointestinal 317 (93.5%), hematologic 311 (91.7%) and musculoskeletal 180 (53.1%). Thirty-nine (11.5%) had 5-7 organ-systems involved. Metabolomics emphasized increased hepatic transaminases 245 (72.3%), lactate dehydrogenase 164 (48.4%) and creatine phosphokinase 84 (24.8%) approaching high thousands (121,560 u/L), both were markers for severe disease (p<0.002). Thirteen (3.8%) received intensive care. Dengue was laboratory-confirmed in 220 (78.9%): NS1 antigen-positive (218); RT-PCR-positive (23), with an overlap of NS1 antigen and RT-PCR positive (21); DENV-3 serotype (20). Seventeen (5%) died, 16 (94.1%) had severe dengue and 11 (64.7%) succumbed within 24 to 48 hours of admission. Conclusion: Severe dengue with increased attributable mortality occurred in hospitalized children after Jamaica’s maiden Zika epidemic.